Réponses

2014-05-09T21:00:16+02:00
Résoudre une équation :

a)
3x + 2 = 2x - 5
3x - 2x = - 5 - 2
x = - 7

b)
- 3x + 7 = 3x - 11.
-3x - 3x = - 11 - 7
- 6x = - 18
x = 18/6
x = 3

a)
2(x - 5) = 3x + 5
2x - 10 = 3x + 5
2x - 3x = 5 + 10
-x = 15
x = -15

b)
-4(3 + x) = 2x - 6
- 12 - 4x = 2x - 6
-4x - 2x = - 6 + 12
- 6x = 6
x = - 6/6
x = - 1

Meilleure réponse !
2014-05-09T21:00:36+02:00
Bonsoir

a) 3x + 2 = 2x - 5
3x -2x = -5 -2
x = -7

 b) - 3x + 7 = 3x - 11.
-3x -3x = -11 -7
-6x = - 18
x = 18/6
x = 3

a) 2(x - 5) = 3x + 5
2x -10 = 3x +5
2x -3x = 5 +10
-x = 15
x = -15

 b) -4(3 + x) = 2x - 6.
-12 -4x = 2x -6
-4x -2x = -6 +12
-6x = 6
x = -1